Variable Absorption of Clavulanic Acid After an Oral Dose of 25 mg/kg of Clavubactin® and Synulox® in Healthy Cats - Tom B. Vree; Eric Dammers; Eri van Duuren (The Scientific World Journal)
The aims of this investigation were to calculate the pharmacokinetic parameters and to identify parameters, based on individual plasma concentration-time curves of amoxicillin and clavulanic acid in cats, that may govern the observed differences in absorption of both drugs. The evaluation was based on the data from plasma concentration-time curves obtained following a single-dose, open, randomised, two-way crossover phase-I study, each involving 24 female cats treated with two Amoxi-Clav formulations (formulation A was Clavubactin® and formulation was B Synulox® ; 80/20 mg, 24 animals, 48 drug administrations). Plasma amoxicillin and clavulanic acid concentrations were determined using validated bioassay methods. The half-life of elimination of amoxicillin is 1.2 h (t1/2 = 1.24 ± 0.28 h, Cmax = 12.8 ± 2.12 μg/ml), and that of clavulanic acid 0.6 h (t1/2 = 0.63 ± 0.16 h, Cmax = 4.60 ± 1.68 μg/ml). There is a ninefold variation in the AUCt of clavulanic acid for both formulations, while the AUCt of amoxicillin varies by a factor of two. The highest clavulanic acid AUCt values indicate the best absorption; all other data indicate less absorption. Taking into account that the amoxicillin–to–clavulanic acid dose ratio in the two products tested was 4:1, the blood concentration ratios may actually vary much more, apparently without compromising the products’ high efficacy against susceptible microorganisms.